A Mycobacterium smegmatis mutant with a defective inositol monophosphate phosphatase gene homolog has altered cell envelope permeability. - Parish, T (1997)
A bacteriophage infection mutant (strain LIMP7) of Mycobacterium smegmatis was isolated following transposon mutagenesis. The mutant showed an unusual phenotype, in that all phages tested produced larger plaques on this strain compared to the parent strain. Other phenotypic characteristics of the mutant were slower growth, increased clumping in liquid culture, increased resistance to chloramphenicol and erythromycin, and increased sensitivity to isoniazid and several beta-lactam antibiotics. Permeability studies showed decreases in the accumulation of lipophilic molecules (norfloxacin and chenodeoxycholate) and a small increase with hydrophilic molecules (cephaloridine); taken together, these characteristics indicate an altered cell envelope. The DNA adjacent to the transposon in LIMP7 was cloned and was shown to be highly similar to genes encoding bacterial and mammalian inositol monophosphate phosphatases. Inositol is important in mycobacteria as a component of the major thiol mycothiol and also in the cell wall, with phosphatidylinositol anchoring lipoarabinomannan (LAM) in the cell envelope. In LIMP7, levels of phosphatidylinositol dimannoside, the precursor of LAM, were less than half of those in the wild-type strain, confirming that the mutation had affected the synthesis of inositol-containing molecules. The impA gene is located within the histidine biosynthesis operon in both M. smegmatis and Mycobacterium tuberculosis, lying between the hisA and hisF genes.